Implementation of Character Education through Children's Language Development in Elementary Schools - Mustoip, Sofyan; Ghozali, Muhammad Iqbal Al; As, Umi Sumiati; Sanhaji, Saleh Youssef (Universitas Muhammadiyah Mataram, 2023)
Character education implementation through language development is essential in primary education. However, the application of character education in reality has not been optimal. This study aimed to explore the implementation of character education through language development in primary schools. This research used a qualitative approach, and data were collected through observation, interviews, and documentation. The population of this study consisted of 522 students and 16 teachers in 15 classes at Silih Asah II State Elementary School in Cirebon City, Indonesia. The research sample was sampled from class 2A, consisting of 40 students, and 10 students' parents also gave feedback regarding this learning. The teacher sample consisted of 5 male and 5 female teachers, including the principal. The results showed that the implementation of character education through language development can be accomplished by combining language development activities with character learning activities such as storytelling, singing, and group games that involve all students. In addition, the results showed that through language development, children can learn communication and social skills that help them build good character. Therefore, this study concluded that language development can be an effective medium for implementing character education in primary schools.